Psychogenic urine retention during doping controls: Consequences for elite athletes - Elbe, A.-M.; Schlegel, M.-M.; Brand, R. (Performance Enhancement & Health, 2012)
Psychogenic urine retention during doping controls (PURD) refers to an athlete`s inability to urinate during a doping control. This paper reports PURD to occur quite frequently in elite athletes, investigates the relationship to the clinical disorder of paruresis (PAR), and investigates its relation to recovery, performance, and self-perception of professionalism and athletic excellence. Furthermore, a scale developed especially for the close description and measurement of PURD is presented. A questionnaire was used for measuring paruresis. The results are based on two online and one paper and pencil study involving 222 German-speaking athletes from various sports. The results indicate that 60% of these athletes have experienced psychogenic urine retention during doping controls, with only 39% of them showing symptoms of paruresis. PURD impacts athlete recovery and self-perception of professionalism and athletic excellence. Suggestions for psychological interventions and recommendations for improving the doping control system are given.